The social, cultural & technological impacts of the Covid-19 pandemic in family farming: the case of Washington State - Centeno, Matías Ezequiel; Garrido, María (Technology & Social Change Group, University of Washington., 2022)
The COVID-19 pandemic has accelerated transformations that we were expecting to happen in decades. The so-called "new normal" gave way to a covidianity characterized by structural instability affecting daily life, the fragility of economic systems and political cycles, speeding up technical shifts, and the dematerialization of human activity, caused by the increasing virtualization of a wide diversity of duties and processes. Even when the agricultural economic outlook illuminates some positive scenarios, farming is familiar with the whirlwind of uncertainties and challenges that have exponentially expanded by the dynamics emerging from the pandemic. Digital technologies catalyze the complex process settled by the pandemic, with cultural, social and technological implications in family farming that this research aims to capture